Planejamento de manutenção preventiva em uma indústria do ramo metal mecânico - Favarin, Rafael Langhinotti (2018)
The current scenario of preventive maintenance of small and medium industries in Brazil in general is not satisfactory. This is due to the lack of investment in planning and control of this maintenance, as well as the interest of the industries in qualifying and inserting qualified professionals in sufficient numbers in this area. Considering this information, this work has the objective of proposing a preventive maintenance plan for a specific industry in the steel industry. For this, interviews were carried out in addition to visits to the site in order to follow up on the maintenance actions of the foundry sector of the company. The company under study presents a high index of corrective maintenance and often there is a lack of organization of preventive maintenance. Aiming to contribute to the study, the data were submitted to a criticality matrix, which resulted in a classification of the machinery of the areas of interest. The preventive maintenance plans for the selected high criticality machines may contribute to the implementation of a preventive maintenance culture in the company.